2021
DOI: 10.1093/advances/nmaa137
|View full text |Cite
|
Sign up to set email alerts
|

Metabolism of Neonatal Vitamin A Supplementation: A Systematic Review

Abstract: A systematic review was conducted to summarize the absorption, transport, storage, and metabolism of oral neonatal vitamin A supplementation (NVAS). This review focused specifically on the neonatal period (first 28 d of life for humans) to inform guidance by WHO on recommendations related to NVAS. A systematic search of international and regional databases was conducted. Inclusion criteria were human or animal studies that gave oral vitamin A as a single or limited number of doses to apparently healthy neonate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 95 publications
0
6
0
Order By: Relevance
“…Studies assessing the relationship between vitamin A intake and a marker of vitamin A status (Excel sheet 2B Intake Status) and between status and health, growth, or development outcomes (Excel sheet 2C Status Outcome) may in combination support the data directly assessing intake and outcomes. For Intake Status studies, we included three systematic reviews published since early 2013 [ 24 , 25 , 26 ], which were data-extracted and assessed for risk of bias (plus two older systematic reviews), 31 recent trials, of which 12 appeared particularly recent and relevant [ 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 ] (and 80 older trials). Alongside these we noted 12 recent cohort or case–control studies, 15 earlier studies, nine recent cross-sectional studies, 25 older studies, and nine non-systematic reviews.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Studies assessing the relationship between vitamin A intake and a marker of vitamin A status (Excel sheet 2B Intake Status) and between status and health, growth, or development outcomes (Excel sheet 2C Status Outcome) may in combination support the data directly assessing intake and outcomes. For Intake Status studies, we included three systematic reviews published since early 2013 [ 24 , 25 , 26 ], which were data-extracted and assessed for risk of bias (plus two older systematic reviews), 31 recent trials, of which 12 appeared particularly recent and relevant [ 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 ] (and 80 older trials). Alongside these we noted 12 recent cohort or case–control studies, 15 earlier studies, nine recent cross-sectional studies, 25 older studies, and nine non-systematic reviews.…”
Section: Resultsmentioning
confidence: 99%
“…The most relevant studies appear on the Excel sheet 2B Intake Status. There are three relevant systematic reviews [ 24 , 25 , 26 ], plus a set of trials assessing effects of supplementation on serum retinol and beta-carotene. Many isotopic studies (shown in Table 2 ) also assessed intake status relationships.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Most carotenoids are found in red and orange fruits and vegetables, such as broccoli, carrots, spinach and sweet potatoes (4). since 2011, vitamin A supplementation is no longer recommended for breastfeeding mothers, as a public health intervention, due to the lack of evidence that it prevents morbidity and mortality in mothers and infants (6). Vitamin A is commonly found in these products in two forms, as palmityl or retinyl acetate.…”
Section: Source Of Vitamin Amentioning
confidence: 99%